Strategic planning to increase the productivity of Consorcio Minero Horizonte in the year 2020 - Loayza Susanibar, Guido Francisco (2022)
The study focused on evaluating the impact of strategic planning on the productivity of the company Consorcio Minero Horizonte in 2020; For this, a quantitative approach research was carried out, of an applied type, descriptive level and non-experimental design, correlational - causal and transectional temporal scope. The documentary review, the survey and the direct observation were used as techniques, and as instruments, the SWOT matrix, the questionnaire and the data collection sheet; a sample of 66 workers was considered. The results determined that 75.8% indicated that various actors (workers, communities, NGOs) are constantly involved in the company's planning activities, while 15.2% considered that, for the implementation of this activity, such actors are never involved. taken into account; The analysis of historical statistics showed that daily productivity decreased, especially in 2020, when it fell by 21%. The conclusions determined that strategic planning positively affects the productivity of the Consorcio Minero Horizonte company in 2020. Likewise, strategic planning can positively influence the performance of the equipment, exploitation performance, production compliance and in reducing operating costs.